Strategi Perencanaan Partisipatif dan Public Relations pada Wisata Edukasi Tanaman Obat dalam Meningkatkan Ekonomi Masyarakat di Desa Jubung Kabupaten Jember - Nur Kamilah (Jurnal Al-Hikmah, 2022)
The concept of educational tourism is tourism that applies non-formal education for tourists through tourism activities and learning with fun methods. And in this study the research subject is a vehicle for tourism that has a significant impact on managers and the community. That is the educational tour of Jubung Jember medicinal plants. At the beginning of this educational tour, there was no dialogue process between the management and the community. There is only a dialogue process between the management and superiors or parties from the campus (University of Jember), the purpose of the meeting is to discuss anything related to medicinal plant education vehicles, and also discuss plants or plants that are lacking in the vehicle, also discuss about how this vehicle became one of the most favored by all circles. This research uses qualitative research. Nelson, Treicher, and Grossberg say that qualitative research is an independent field of inquiry. Meanwhile, the strategy of the management of the Jubung Jember medicinal park tourism is as follows: 1. Strategy with the Participatory Planning Concept is the planning and decision-making process in development programs which are often carried out from top to bottom (top Don planning). 2. The second strategy is a strategy by directly involving the community in the procurement of educational tourism at the drug park. 3. The third strategy is to fulfill the concept of community empowerment. an increase every year before this pandemic period in 2017 got more around Rp. 10,000,000 in 2018 earned Rp. 15,000,000 in 2019 decreased greatly due to the covid-19 pandemic that attacked our activities, so that all activities did not run according to instructions, which only received as much as Rp. 2,000,000. So it can be seen at the time the Medicine Park was established, it can be concluded from the report above that there was an increase in income in 3 years. Not only that, this has an impact on the economic life of the surrounding community who sell near Jubung Jember Drug Tourism.